Effect of social media addiction toward academic performance among university students - Chai, Wing Kit (2023)
Since the invention of social media, the connection between each other have become closer than ever as social media have multiple features and functions that allow us to keep up with the world and also communicate with others. However, while social media have been useful it also been showing different undesired effects as pervious researched shown that social media will negative effect on working performance among the work force and also academic performance among university students. This research is to determine the seriousness of social media addiction among university students and also determine the impact of social media addiction toward academic performance of university students. Quantitative method has been used to gather information through Google Form and SPSS will be used for data analysis same goes as Google Excel and Google Form. Uses and Gratification Theory and Brain Disease Model of Addiction theory will also be used for theoretical framework. Result have shown that university student is heavily addicted towards social media and their academic performance have been affected due the addiction. This result shows that university need to create ways to decrease the usage of social media among university student in order to prevent decrease of academic performance.